Everyday aesthetics and the dichotomy between routine and charisma - Aslani, Stella (Ars et humanitas, 2023)
Everyday aesthetics, at its core, is based on the supposed dichotomy between art and life, considering life as something routine-like, and art as the breaking of the routine, something charismatic. Different authors of everyday aesthetics use different words to describe this dichotomy. For example, in his article “What is ‘Everyday’ in Every-day Aesthetics?”, Ossi Naukkarinen simply uses everydayness and non-everyday-like, while Arto Haapala, in his “On the Aesthetics of the Everyday: Familiarity, Strange-ness, and the Meaning of Place” uses the terms familiarity and strangeness. The au-thors also propose different ways of bridging this dichotomy. However, as the paper shows, the real question is not how to bridge the dichotomy itself but rather whether the dichotomy exists in the first place. Moreover, the paper suggests a change of direc-tion in future investigations of everyday aesthetics, and focusing on the nuances that exist on the routine-charisma and charismatic-routine spectrum, supported by aca-demic research and the personal account of the paper’s author art project. Moreover, the implications of this shift extend beyond the boundaries of everyday aesthetics.
Keywords: Estetika; Filozofija; Karizma